Kelangsungan Hidup Larva Ikan Betok (Anabas testudineus Bloch) Dengan Pemberian Pakan Alami Hasil Pemupukan Pada Media Air Gambut - Suriansyah Suriansyah (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2012)
Different percentage of natural food can improve the survival rate of swim fry climbing perch (Anabas testudineus Bloch) till seed, because the size of natural food is suitable to opened mouth of swim fry after finished yellow egg. Growth of swim fry is determined by existence natural food and obstetrical of nutrition food function to increase growth till seed size. The aims of this research are to know the effectivity use of filtered natural food for survival rate and relative growth of swim fry climbing perch till seed. The result of this research are 20 liters filter of natural food can improve the survival rate 75% and relative growth swim fry climbing perch 15000% for 30 days experiment.